Developing Intercultural Communicative Competence in an Early EFL Classroom: A Case Study of an Extra-Hour Conversation Program - Rini, Setia; Nida, Nur Lailatun (UIN Salatiga, 2026)
Research on English language teaching in primary school contexts has increasingly emphasized the importance of early communicative and intercultural learning. However, limited studies have examined how supplementary English programs function as micro-level language policy spaces in developing intercultural communicative competence (ICC). Situated in the Indonesian early EFL context, where English at the primary level is optional and unevenly implemented, this study investigates an extra-hour English Conversation Program in a private primary school. This article reports a qualitative case study that explores how the program operates as a micro-level language policy space in shaping students’ intercultural communicative competence, as well as their linguistic development and learning motivation. It also examines how students experience the program differently, and how teacher agency, institutional practices, and socio-cultural factors mediate participation, equity, and sustainability. Data were collected through classroom observations, teacher interviews, and analysis of instructional practices. The findings indicate that the program creates meaningful opportunities for early intercultural encounters through interactive speaking activities and exposure to authentic language use, fostering students’ confidence, willingness to communicate, and openness to cultural diversity. However, students’ participation is uneven, influenced by prior English exposure, teacher mediation, and institutional support. This study argues that the development of intercultural communicative competence in early EFL classrooms is not solely a result of increased language exposure but is shaped by locally enacted language policies and everyday classroom practices. The findings highlight the importance of designing equitable and sustainable supplementary programs to support ICC development in primary EFL contexts.